COVID‐19 大流行中的妊娠糖尿病:中国杭州的一项回顾性研究 - Binbin Yin; Kaiqi Wu; Lingwei Hu; Wanlu Zheng; Yidan Zheng; Xiuzhi Duan; Bo Zhu (Journal of Diabetes, 2022)
Abstract Aims Our study aimed to investigate changes in the prevalence of gestational diabetes mellitus (GDM) in the COVID‐19 pandemic and postpandemic era and the risk of adverse pregnancy outcomes in pregnant women diagnosed with GDM during the blockade period. Methods First, we investigated changes in the prevalence of GDM and the population undergoing oral glucose tolerance tests (OGTT) after the COVID‐19 pandemic. We then collected clinical information from pregnant women diagnosed with GDM to explore the risk of adverse pregnancy outcomes in pregnant women with GDM during the COVID‐19 pandemic. Results After the COVID‐19 pandemic, the proportion of pregnant women in the total number of outpatient OGTT tests decreased yearly. The ratio was 81.30%, 79.71%, and 75.48% from 2019 to 2021, respectively, with the highest proportion of pregnant women in February 2020 (92.03%). The prevalence of GDM was higher in March 2020 compared to the same period in 2019. However, from 2019 to 2021, the prevalence decreased year by year with 21.46%, 19.81%, and 18.48%, respectively. The risk of adverse pregnancy outcomes for pregnant women diagnosed with GDM during the most severe period of the COVID‐19 pandemic did not differ from before the COVID‐19 pandemic. Conclusions After the COVID‐19 pandemic, the prevalence of GDM increased during the most severe period of the epidemic, but the overall prevalence of GDM decreased year by year. In addition, the pandemic did not change the risk of adverse pregnancy outcomes in pregnant women with GDM.